A new ferrocene/disulfide-containing methacrylate monomer: Synthesis, ATRP and nanocomposite. (October 2019) - Qian, Wenhao; Zhang, Haiyan; Song, Tao; Ye, Mao; Feng, Chun; Lu, Guolin; Huang, Xiaoyu
Graphical abstract: This article reports a new ferrocene/disulfide-containing methacrylate monomer and its nanocomposite via surface-initiated ATRP. Highlights: A new ferrocene/disulfide-containing methacrylate monomer, FcMAss, was prepared through successive esterification. PFcMAss homopolymer and PEG- b -PFcMAss diblock copolymer were prepared via ATRP. Graphene oxide-based nanocomposite was prepared by surface-initiated ATRP of FcMAss via the grafting-from strategy. Abstract: A new methacrylate monomer containing ferrocene unit and disulfide bond, 2-((2-(methacryloyloxy)ethyl)disulfanyl)ethyl ferrocenecarboxylate (FcMAss), was prepared by subsequent esterification reaction with bis(2-hydroxyethyl) disulfide and methacryloyl chloride using ferrocenecarboxylic acid as starting material. A series of well-defined poly(2-((2-(methacryloyloxy)ethyl)disulfanyl)ethyl ferrocenecarboxylate) (PFcMAss) homopolymers with narrow molecular weight distributions ( M w / M n < 1.30) was then obtained by atom transfer radical polymerization (ATRP) of FcMAss monomer in toluene. Block copolymerization of FcMAss monomer was initiated by PEG-Br macroinitiator in THF to afford a poly(ethylene glycol)- b -poly(2-((2-(methacryloyloxy)ethyl)disulfanyl)ethyl ferrocenecarboxylate) (PEG- b -PFcMAss) diblock copolymer with a relatively low dispersity ( M w / M n = 1.34). Graphene oxide (GO)-based nanocomposite, GO-PFcMAss, was prepared by surface-initiated ATRP of FcMAss via the grafting-from strategy, using GO-based macroinitiator obtained by treating tris(hydroxymethyl) aminomethane (TRIS)-modified GO with 2-bromo-2-methylpropionyl bromide. The nanocomposite was characterized by FT-IR and XPS, and showed excellent dispersibility and colloidal stability.